2013
DOI: 10.1155/2013/872632
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Ankylosing Spondylitis, Crohn’s Disease,Klebsiella, and Starch Consumption

Abstract: Both ankylosing spondylitis (AS) and Crohn's disease (CD) are chronic and potentially disabling interrelated conditions, which have been included under the group of spondyloarthropathies. The results of a large number of studies support the idea that an enteropathic pathogen, Klebsiella pneumoniae, is the most likely triggering factor involved in the initiation and development of these diseases. Increased starch consumptions by genetically susceptible individuals such as those possessing HLA-B27 allelotypes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 74 publications
1
47
0
3
Order By: Relevance
“…Since these tests have high sensitivity and specificity, they could be used for AS patients by clinicians. AS and IBD may accompany each other, which means a fecal calprotectin test in AS patients may be used in the early diagnosis of IBD and in patient monetarization [18]. Our study has some limitations.…”
Section: Discussionmentioning
confidence: 90%
“…Since these tests have high sensitivity and specificity, they could be used for AS patients by clinicians. AS and IBD may accompany each other, which means a fecal calprotectin test in AS patients may be used in the early diagnosis of IBD and in patient monetarization [18]. Our study has some limitations.…”
Section: Discussionmentioning
confidence: 90%
“…K. pneumoniae has also been identified as a causative agent of other less common, yet serious, infections such as liver abscess and invasive syndrome (39, 40), septic arthritis (41), or generalized pustulosis (42), and as the triggering factor in the initiation and development of ankylosing spondylitis and Crohn's disease (43-45). K. pneumoniae strains have accumulated plasmids that carry virulence and resistance genes that keep increasing its ability to resist the main antibiotics used for treatment such as cephalosporins, carbapenems, penicillins, aminoglycosides or fluoroquinolones (26, 37, 38, 46, 47).…”
mentioning
confidence: 99%
“…(32) food supplements in the past 2 weeks of use the most common were omega-3 (13), multivitamin and/or multimineral (12) …”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that a low starch diet leads to lower AS disease activity and that Klebsiella pneumoniae, which can be influenced by starch consumption, is a triggering factor involved in the initiation and development of AS (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%